Development Of Instructional Design Project-Based Learning Model Integrated Science Process Skills To Improve Science Literacy - Edy Waluyo; Nuraini Nuraini (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2021)
Facing today's 21st century learning, teachers need to foster science literacy and consider learning strategies that suit the conditions and potentials of students whose learning process focuses on providing hands-on experience and the application of science knowledge. Literacy skills are fundamental things that students must do in the face of the global era to be able to meet the needs of life in various situations. This research aims to develop instructional design through science process skill-based project learning to improve valid, practical and effective literacy skills. This research uses a type of research development model Borg and Gall which is a systemic process that starts from the analysis of needs, product design, product development, implementation and evaluation of products. The subjects in the research were grade VII students smpn 1 Selong and Madrasah Tsanawiyah Muallimat NW Pancor numbered 64 people. Data collection uses validation sheets, practical guidelines, and tests to measure students' science literacy skills. The data is analyzed with descriptive analysis techniques. The results of the analysis showed that the instructional design of the project based learning model based on science process skills falls into the category of valid, practical and effective and feasible to use. The product developed also has a potential effect in improving students' science literacy skills indicated by an N-Gain score of 0.77 with a high categoryKeywords : Project Based Learning, Process Skills, Literacy